Cyclic compressive behavior of seawater sea-sand concrete after seawater freeze–thaw cycles: Experimental investigation and analytical model. (22nd August 2022) - Zhou, Junlong; Li, Dongsheng
Graphical abstract: Highlights: The frost durability of normal-strength and high-strength air-entraining seawater sea-sand concrete (SSC) was evaluated. Cyclic compressive behavior of SSC after seawater freeze–thaw cycles (FTCs) was studied. The service life of SSC offshore structures in cold regions was recommended. An analytical model was proposed to predict the cyclic compressive stress–strain behavior of SSC after seawater FTCs. Abstract: Due to its economic benefit and environmental friendliness, seawater sea-sand concrete (SSC) has much potential to replace conventional concrete in the future. However, the mechanism of SSC after freeze–thaw cycles (FTCs) is obscure. This paper reports the results of an experimental investigation on the cyclic compressive stress–strain behavior of normal- and high-strength air-entraining SSC after seawater/freshwater FTCs. Environment-friendly supplementary cementitious materials (SCMs) were used in the SSC mixture to ensure considerable durability. The experimental results showed that seawater FTCs seriously deteriorated the anti-peeling ability and mechanical performance of normal-strength SSC. The compressive strength, modulus of elasticity, and Poisson's ratio of SSC decreased severely, and the peak strain increased after seawater FTCs. The ability of SSC to resist seawater FTCs was significantly affected by the concrete grade. High-strength SSC had excellent resistance to seawater FTCs. In contrast, freshwater FTCs hardly affected the performance of SSC. The degradation of SSC caused by seawater FTCs could be attributed to increased capillary pores and cracks in the matrix by MIP, XRD, and SEM results. Based on the test results, the potential concrete grade of SSC offshore structures is recommended in (severe) cold regions to ensure the expected service life. In addition, this paper presents an analytical model to predict the cyclic axial compressive stress–strain behavior for SSC after seawater FTCs. The model consists of the envelope curve, the unloading model in quadratic parabolic, and the linear reloading model. The test results and analytical model could provide engineers with a basic design guideline for applying SSC to offshore structures subjected to the unfavorable combination of seismic loading and cold environments.